Nuanced Account Management Driving Excellence in B2B Sales - Shankar, Bala (Springer Singapore, 2018)
"Nuanced Account Management is a 'how to' book. Born out of insights gained over two decades in the B2B industry, the book presents a comprehensive and practical approach to delighting customers and driving profitability. Powerful thoughts expressed in a simple and easy to read style." - Nitin Paranjpe, President, Homecare, Unilever "Nuanced Account Management is a must read for any B2B salesperson. It provides detailed, specific advice on how to become a more customer-centered advisor in the complex world of business to business transactions." -Bernie Jaworski, The Peter Drucker Chair in Management, Drucker School of Management, Claremont Graduate University, USA "The art of selling and building a partnership with your client is often undervalued. "Nuanced", as Bala Shankar describes, is a perfect word that continues the process of building a lasting trust with another business with an existing customer, trust based on all the factors he describes in detail, highs and lows you will face. Experience and differentiation are increasingly keys today and I fully recommend this profound and very practical guide." -Roger Schmid, Global Innovation Advisor, The Natura Group, USA & Brazil This book is a comprehensive practical guide for account managers, sales teams and account leaders operating in the B2B space. It provides knowledge to excel in developing, growing and retaining top accounts in local and global environments. With a nuanced version of 'account management' that will potentially be a game changer, the book offers a personnel-and-process based agenda that can create a 'competitive advantage' on its own. Bala Shankar is a consultant and has been an adjunct marketing faculty at the Singapore Management University (SMU) for nearly a decade. He has had 25 years of corporate experience in Asia, Europe, and North America in various sales and account management capacities as a regional and global leader. Bala has also been associated with executive development programs and is a contributing writer to The Business Times, Singapore. He received his MBA from the renowned Indian Institute of Management (IIM), Ahmedabad.